MAGMATISM AND GEODYNAMICS OF THE SOUTHERN BAIKAL VOLCANIC REGION (MANTLE HOT SPOT): RESULTS OF GEOCHRONOLOGICAL, GEOCHEMICAL, AND ISOTOPIC (SR, ND, AND O) INVESTIGATIONS - Yarmolyuk V.V.; Kovalenko V.I.; Ivanov V.G.; Pokrovskii B.G. (My University, 2003)
The results of geochronological, geochemical, and isotopic investigations for magmatism and geodynamics of the Southern Baikal Volcanic region (mantle hot spot) are presented. The data presented suggest that the formation of the volcanic region has continued for 30 My. However, its development was not continuous and occurred through activity pulses, which are distinguished as stages in the volcanic history of the region.